Power Relations Between Parents and Children as Seen in Desni Intan Suri's Aku Tidak Membeli Cintamu and Mohja Kafh's The Girl in Tangerine Scarf - Handayani, Rika (Vivid: Journal of Language and Literature, 2023)
The role of parents in determining the lives of their children has been depicted in many media including literary works. This article tries to show how this issue is presented in two novels. Scrutinized from Foucauldian's perspective focusing on power relations between parents and children, this article analyzes Desni Intan Suri's Aku Tidak Membeli Cintamu and Mohja Kafh's The Girl in the Tangerine Scarf. The results show that the parents impose their power in the form of domination. In addition, the authors portray the children's acceptance as well as resistance to domination. Acceptance indicates obedience. On the other hand, resistance is a way to exemplify that parents' dominations can be challenged as children's voices are also valuable.